Programs and Prognoses - Streeten, Paul (Quarterly Journal of Economics, 1954)
I. Is and ought, 355. — II. Program and prognosis, 357. — III. Program determined by prognosis, 359. — IV. Prognosis determined by program, 360; programs as social data, 361; selection and relevance, 361; models and concepts: the index number problem, 362; inadequacy of the means-ends schema, 364; implications for welfare economics, 367; ideologies, 368. — V. Interdependence between program and prognosis, 369; prophecies: cure through prognosis, 369; dangerous thought: destruction through prognosis, 370; harmony through prognosis, 372; speculation and oligopoly, 374. — VI. The task of the social sciences, 374. — VII. Summary, 376.